An apple for the creature [large type] - Harris, Charlaine; Kelner, Toni L. P. (Wheeler Publishing, 2013)
Your worst school nightmares will pale in comparison to these thirteen original stories of academic anxiety. You'll need more than an apple to stave off the creatures in Harris's never-before-published Sookie Stackhouse story, Ilona Andrews' tale of "exceptional" children, Thomas Sniegoski's "Bad Hour" at dog obedience school, and ten more. Remember your first lesson: resistance is fruitless!